The Manifestation of Internalized Sexism in the Pick Me Girl Trend on TikTok - Ida Rosida; Meka Mona Ghazali; Dania Dedi; Fanya Shafa Salsabila (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2022)
Internalized sexism focuses on the forms of sexist behaviour and attitudes conducted by women toward themselves and other women. This article discusses the internalized sexism on TikTok videos tagged with “Pick Me Girl” or the hashtag #PickMeGirl. It can be defined as a social media phenomenon dominated by women who always consider that they are the best in any kind of condition. As they are feeling perfect, they easily hate, insult, and compete with other women. The method used is qualitative. The data was collected by focusing on Pick Me Girl videos on TikTok and giving a critical understanding of the languages the women used in the video. This study was working within the theoretical framework of misogyny by Kate Manne and the concept of internalized sexism. This study aims to explore Pick Me Girl’s sexist behaviors and attitudes and investigate the relationship between women. The results show that Pick Me Girl on TikTok presents the ideas of beauty standard which differ among women, competition between women to get men’s attention, women’s self-objectification, and humiliation toward other women. Although the competition eventually destroys the other women, this characteristic offers pleasure to Pick Me Girl women. Internalized misogyny subsequently leads women to insult other women, hatred other women, and decrease other’s women’s values. Internalized sexism is obviously seen through their actions on social media.